FAKTOR KONTINUITAS POLITIK LUAR NEGERI MESIR TERHADAP AMERIKA SERIKAT PASCA REVOLUSI 2011 - Hafid Adim Pradana (UNIDA Gontor, 2017)
Revolution happening in a country often impact on the country’s foreign political change. However, the revolution that occurred in Egypt in 2011, followed by the election of Mohammed Morsi of the Muslim Brotherhood as the first civilian president of Egypt, it did not change the foreign policy of Egypt, particularly against the United States. In that sense, Egypt is still continuing good relations with the United States as in the reign of Hosni Mubarak. This research aims to explain the factors that affect no change in Egypt’s foreign policy towards the United States after the revolution of 2011, especially in the era of Mohammad Mursi. In this study, the authors use the neoclassical realism theory which states that the foreign policy adopted by a country is the result of domestic political dynamics that are influenced by international structures. By using literature data collection, this study resulted in the finding that no change in the foreign policy of Egypt during the reign of Mohammad Mursi against the United States is affected by international structures which then impact on Egypt’s position which acts as a buffer state of peace in the Middle East.This in turn affects the occurrence of domestic political dynamics that make Mursi Egypt decided not to change Egypt’s foreign policy toward the United States.